Early LV remodelling patterns in overweight and obesity: Feasibility of cardiac CT to detect early geometric left ventricular changes. Issue 5 (September 2019) - Walpot, Jeroen; Inácio, João R.; Massalha, Samia; El mais, Huda; Hossain, Alomgir; Shiau, Judy; Small, Gary R.; Crean, Andrew M.; Yam, Yeung; Rybicki, Frank; Chow, Benjamin J.W.
Abstract: Background: Obesity is an in independent risk factor for cardiovascular disease. Goal: To describe the early LV remodelling pattern in patients with overweight and obesity and structurally normal hearts. Methods: Consecutive patients (n = 2374), with structurally normal hearts and BMI ≥ 18.5 kg/m 2, undergoing prospective mid-diastolic ECG gated CTCA were selected. Left ventricular mass (LVM) and Left ventricular mid-diastolic volume (LVMDV) were measured. The concentricity index (LVM/LVMDV) were calculated. According to the definitions of the World Health Organization (WHO), the patients were divided into weight categories. Results: The mean LVM ± Std. deviation in the subgroups according to WHO classification was 101.68 ± 28.99 g (normal weight), 115.79 ± 29.14 g (overweight), 123.8 ± 33.44 g (class I obesity), 125.85 ± 32.89 g (class II obesity) and 132.45 ± 37.85 g (class III obesity). (p < 0.001) The mean LVMDV progressed with increasing WHO weight category from 112.37 ± 36.46 in patients with normal BMI to 140.26 ± 43.78 in patients with class III obesity. (p < 0.001) The concentricity index was 0.935 ± 0.216 g/ml in patients with normal BMI, 0.979 ± 0.253 g/ml, 1.058 ± 0.635 g/ml, 0.996 ± 0.284 g/ml and 0.9768 ± 0.244 g/ml in patients with BMI categories 25–29.99, 30–34.99, 35–39.99 and ≥40 kg/m 2, respectively. Conclusions: Our study demonstrates a non-linear (inverse U-shape) relationship between increasing BMI class and concentricity index, reaching its maximum at a BMI of 30–34.99 kg/m 2 . Further increase in BMI results in LV dilation.